2019
DOI: 10.18632/oncotarget.27367
|View full text |Cite
|
Sign up to set email alerts
|

p53-inducible SESTRINs might play opposite roles in the regulation of early and late stages of lung carcinogenesis

Abstract: SESTRINs (SESN1-3) are proteins encoded by an evolutionarily conserved gene family that plays an important role in the regulation of cell viability and metabolism in response to stress. Many of the effects of SESTRINs are mediated by negative and positive regulation of mechanistic target of rapamycin kinase complexes 1 and 2 (mTORC1 and mTORC2), respectively, that are often deregulated in human cancers where they support cell growth, proliferation, and cell viability. Besides their effects on regulation of mTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Furthermore, while it was reported that AKAP1 is capable of stimulating the activity of mTORC1, and SESN2 can counteract its effect, we were not able to observe any notable difference in the mTORC1 activity between control and SESN1-and/or SESN2-deficient cells incubated under standard cell culture conditions. These data indicate no negative effects of SESN1 and SESN2 on the mTORC1 activity despite the proposed role of AKAP1 in this process [35,36]. We also demonstrated that while SESN2 does not affect GATOR2 localization on the mitochondria, GATOR2 facilitated mitochondrial localization of SESN2, supporting the idea that AKAP1 is probably dispensable for this process (Figs 3 and 4).…”
Section: Plos Onesupporting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, while it was reported that AKAP1 is capable of stimulating the activity of mTORC1, and SESN2 can counteract its effect, we were not able to observe any notable difference in the mTORC1 activity between control and SESN1-and/or SESN2-deficient cells incubated under standard cell culture conditions. These data indicate no negative effects of SESN1 and SESN2 on the mTORC1 activity despite the proposed role of AKAP1 in this process [35,36]. We also demonstrated that while SESN2 does not affect GATOR2 localization on the mitochondria, GATOR2 facilitated mitochondrial localization of SESN2, supporting the idea that AKAP1 is probably dispensable for this process (Figs 3 and 4).…”
Section: Plos Onesupporting
confidence: 74%
“…To determine whether SESN2 interacts with Mios on the mitochondria, we immunoprecipitated endogenous SESN2 from mitochondrial fraction using an anti-SESN2 antibody as previously described [20] and analyzed the presence of Mios in the SESN2 immunoprecipitates. As a negative control, we also analyzed mitochondrial lysates from the cells where SESN2 was knocked out with CRISPR/Cas9 [35]. While we were able to detect Mios in the immunoprecipitates from control cells, indicating that these proteins interact on mitochondria, we did not observe any presence of Mios as well as SESN2 protein in the immunoprecipitated samples from SESN2-deficient cells ( Fig 3A).…”
Section: Sesn2 Is Co-localized With Gator2 Complex On Mitochondriamentioning
confidence: 91%
See 1 more Smart Citation
“…Based on these results, we suggest that Sestrin2 has oncogenic effects in lung cancer cells. Consistently, lung cancer cells from Sestrin2-deficient mice showed slower growth rates than did those from wild type mice [38]. However, Sestrin2 knockdown has also been reported to promote proliferation of cancer cells, inhibit apoptosis of cells [38][39][40], and enhance migration in the wound healing assay [40], which is in complete contrast to our results.…”
Section: Discussionsupporting
confidence: 58%
“…Consistently, lung cancer cells from Sestrin2-deficient mice showed slower growth rates than did those from wild type mice [38]. However, Sestrin2 knockdown has also been reported to promote proliferation of cancer cells, inhibit apoptosis of cells [38][39][40], and enhance migration in the wound healing assay [40], which is in complete contrast to our results. Several previous studies have reported that Sestrin2 can work as a tumor suppressor gene in various cancers [20][21][22].…”
Section: Discussionsupporting
confidence: 58%